1996
DOI: 10.1520/jfs15411j
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Approach to Adult Human Age Estimation from Dental Observations by Johanson's Age Changes

Abstract: Much of the data which appears in the forensic and archaeological literature is ordinal or categorical. This is particularly true of the age related indicators presented by Gustafson [1] in his method of human adult age estimation using the structural changes in human teeth. This technique is still being modified and elaborated. However, the statistical methods of regression analysis employed by Gustafson and others are not particularly appropriate to this type of data, but are still employed because alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 13 publications
2
97
1
2
Order By: Relevance
“…Age estimation methods do not produce specific point estimates of estimated age, but rather, estimated intervals of age (e.g., [45][46][47][48][49][50][51][52][53][54][55]. Thus, the extreme of the age range nearest to the chronological age was used to calculate the bias and the absolute error of the estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Age estimation methods do not produce specific point estimates of estimated age, but rather, estimated intervals of age (e.g., [45][46][47][48][49][50][51][52][53][54][55]. Thus, the extreme of the age range nearest to the chronological age was used to calculate the bias and the absolute error of the estimation.…”
Section: Methodsmentioning
confidence: 99%
“…See, for instance, Masset (1982, 1996); Frankenberg (1992, 1994); Lucy et al (1996); Konigsberg et al (1997); Aykroyd et al (1997Aykroyd et al ( , 1999; Hoppa and Vaupel (2002b). Several authors have suggested that regression techniques result in systematic under-or over-aging of skeletons (Konigsberg and Frankenberg, 1994;Konigsberg et al, 1997;Aykroyd et al, 1997Aykroyd et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a variety of other statistical methods have been explored with the aim of eliminating this apparent bias (e.g. Konigsberg and Frankenberg (1992, 1994; BouquetAppel and Masset (1996); Lucy et al (1996); Konigsberg et al (1997); Aykroyd et al (1997Aykroyd et al ( , 1999; Boldsen et al (2002); Konigsberg and Herrman (2002)). This research has culminated in the book 'Paleodemography', edited by Hoppa and Vaupel (2002b), in which the authors conclude that aging of skeletal remains should utilise methods based on an application of Bayes' theorem in order to obtain age-at-death estimates.…”
Section: Introductionmentioning
confidence: 99%
“…The most used methods include simple linear regression, multiple linear regression [9], classical calibration [10], methods based on analysis of nearest neighbours [11], inverse linear calibration, nonlinear inverse calibration, curvilinear regression [12] and Bayesian approaches [13][14]. This latter approach is not entirely new, having already appeared in a somewhat different framework, in the literature on fisheries, with the name of ``age length key''.…”
Section: Introductionmentioning
confidence: 99%
“…These samples and the scoring system of the two indicators were used by Schmitt et al (2002), applying the methodology proposed by Lucy et al (1996). In the present work, the same data was processed using a modification of the empirical method proposed by Lucy et al (2002).…”
mentioning
confidence: 99%